Enhancing Learning Quality through Effective Classroom Management: A Qualitative Study in Indonesian Elementary Schools - Khaeroni, Khaeroni; Rachmiati, Wida; Mutiara, Anggita (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
The objective of this research is to examine the implementation of classroom management, identify supporting and inhibiting factors in classroom management, and understand the efforts to improve the quality of learning through classroom management. This qualitative study, conducted at SD Negeri Cigelam 2 in Serang, Banten, involves 5th-grade students and a teacher. Data collection techniques include interviews, observations, and documentation. The study employs the Strauss and Corbin Model for data analysis. The findings indicate that classroom management has been effectively implemented, employing principles and approaches in the learning process. Supporting factors include conducive facilities, adequate learning resources, student preparedness, and school-community collaboration. Inhibiting factors encompass the transformative impact of the pandemic, limited resources, human resource constraints, lack of result analysis, varying student qualities, and disruptions. Strategies for improving learning quality through classroom management involve adapting learning materials, creating a comfortable classroom environment, implementing meaningful disciplinary actions, and maximizing teaching effectiveness. The study contributes to the literature by providing insights into the practical application of classroom management principles in an Indonesian elementary school setting.